A Mobile WiMAX Architecture with QoE Support for Future Multimedia Networks - Jailton, José; Carvalho, Tássio; Valente, Warley; Frânces, Renato; Abelém, Antônio; Cerqueira, Eduardo; Dias, Kelvin (IntechOpen, 2012)
None